Migrant Crossing Borders: Bridging Cultural Difference and Securing a Third Space in the Host Country - Tri Murniati (Faculty of Humanities, Universitas Jenderal Soedirman, 2020)
Being migrant workers means being ready to face and accept the challenge of cultural differences in the host country. Bridging in two different cultures, this involves adaptation. However, the process of adaptation—welcoming, embracing and finally accepting—to the host country’s culture is not easy. Tearing between the two different worlds, their migrant experience can be torturous. These migrants are not only transitioning into a new life in the host country but also translating a new culture in their new life phase. Such experiences, then, open up a space—an interstice—which enables these migrants to survive in the new life, the migrant life. Taking, observing, and interpreting the stories of the Indonesian domestic workers (IDWs) in Hong Kong, I argue that these women are able to not only translate but also adoptthe new culture of the host country through assimilation, acculturation and the invention of a common ground, a third space in which they are able to feel like home in the host country. In addition, the process of acculturation involves negotiation which allows IDWs to find a middle ground between two different cultures and the third space illustrates their adjustment in bridging and crossing the cultural border between the home and the host countries. Between Indonesia and Hong Kong, Victoria Park arises as a comfort space which can ease the pain of being stranger in Hong Kong.